Detection of CYP2D6 polymorphism using Luminex xTAG technology in autism spectrum disorder: CYP2D6 activity score and its association with risperidone levels. Issue 2 (April 2016) - Vanwong, Natchaya; Ngamsamut, Nattawat; Hongkaew, Yaowaluck; Nuntamool, Nopphadol; Puangpetch, Apichaya; Chamnanphon, Montri; Sinrachatanant, Ananya; Limsila, Penkhae; Sukasem, Chonlaphat
Abstract: CYP2D6 is involved in the biotransformation of a large number of drugs, including risperidone. This study was designed to detect CYP2D6 polymorphisms with a Luminex assay, including assessment the relationship of CYP2D6 polymorphisms and risperidone plasma concentration in autism spectrum disorder children (ASD) treated with risperidone. All 84 ASD patients included in this study had been receiving risperidone at least for 1 month. The CYP2D6 genotypes were determined by Luminex assay. Plasma concentrations of risperidone and 9-hydroxyrisperidone were measured using LC/MS/MS. Among the 84 patients, there were 46 (55.42%) classified as EM, 33 (39.76%) as IM, and 4(4.82%) as UM. The plasma concentration of risperidone and risperidone/9-hydroxyrisperidone ratio in the patients were significant differences among the CYP2D6 predicted phenotype group ( P  = 0.001 and P  < 0.0001 respectively). Moreover, the plasma concentration of risperidone and risperidone/9-hydroxyrisperidone ratio in the patients with CYP2D6 activity score 0.5 were significantly higher than those with the CYP2D6 activity score 2.0 ( P  = 0.004 and P  = 0.002 respectively). These findings suggested that the determination of the accurate CYP2D6 genotype-predicted phenotype is essential in the clinical setting and individualization of drug therapy. The use of the Luminex assay for detection of CYP2D6 polymorphisms could help us more accurately identify an individual's CYP2D6 phenotype.